2005
DOI: 10.1007/s00404-004-0710-2
|View full text |Cite
|
Sign up to set email alerts
|

Uncommon complications of sacrospinous fixation for treatment of vaginal vault prolapse

Abstract: Etiological factors and treatment considerations for these uncommon complications of sacrospinous colpopexy are discussed in detail, and prophylactic measures, when applicable, are emphasized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…8 Most of these hernias appear within 1 year following the surgery, 1 which is what occurred in the present case (at * 6 months). The anterior types of perineal hernias, categorized based on their position relative to the transverse perineal muscle, occur exclusively in females.…”
Section: Discussionmentioning
confidence: 59%
“…8 Most of these hernias appear within 1 year following the surgery, 1 which is what occurred in the present case (at * 6 months). The anterior types of perineal hernias, categorized based on their position relative to the transverse perineal muscle, occur exclusively in females.…”
Section: Discussionmentioning
confidence: 59%
“…There are also a few case reports on debilitating complications following SSLF such as perineal necrotising infection, perineal herniae, left lateral enterocoele after right SSLF (Silva-Filho et al 2005), ischiorectal abscess (Hibner et al 2005) and myositis of the gluteal region (Faber et al 2008). Pohl and Frattarelli (1997) concluded that the bilateral suspension is different from the unilateral suspension in that the former requires significant intraoperative judgement in its feasibility and in maintaining the width of the vaginal cuff to allow a bilateral suspension without tension.…”
Section: Results and Complicationsmentioning
confidence: 96%